Open our visualization eyes, individualization: On Albrecht Dürer's 1515 wood cut celestial charts. (April 2020) - d'Auriol, Brian J
The position that visualization is an intimate part of human existence and associated with the human species is advanced in this work: visualization abounds delimited by the space of individuality across human history. Visualization involves two complementary aspects of the uniqueness deemed of individuals: individualization reflects individuals' capabilities and personalization reflects designs that seek compatibility with individuals' capabilities. This has a number of implications upon the design and evaluation of visualizations. For one, a suitable visualization model that expresses individualization and personalization is needed: a brief survey of models is presented. For another, addressing intellectual uniqueness requires deep analysis and selective objective balance due to the potentially humongous number of unique ideas that support visualization design and viewer experiences. The Engineering Insightful Serviceable Visualizations model is selected as a guide for a comprehensive visualization evaluation of Albrecht Dürer's 1515 celestial charts. Motivating this choice of visualization is its significance as the first notable and influential European star chart intended for scientific use and mass viewership, and as a blending of science and art. In addition, there is a lack of discussion concerning this particular visualization in the visualization literature. Concluding remarks suggest the significance of approaching visualization from this point-of-view.